STRUKTUR DAN KOMPOSISI BEBERAPA JENIS BURUNG DAN NEKTON DI MANGROVE KAWASAN SEGORO ANAK TAMAN NASIONAL ALAS PURWO - , Marcus Jacoub J Latupapua; , Dr. Erny Poedjirahajoe, MP. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
One indicator of the optimal and the sustainability of mangrove forest condition is the level of diversity of flora and fauna which are owned by the mangrove forest. Diversity of species is to know the parameters used in a community. This parameter characterizes the species richness and balance in a community. Mangrove areas Segoro Anak in Alas Purwo National Park at Bayuwangi district has a diversity of wildlife birds and nekton are quite high. The purpose of this study was to determine the diversity, abundance and species richness of birds and nekton, the relationship between vegetation diversity and feed density of birds on animal diversity and the relationship between physical environmental factors with nekton diversity at permanent plots in the area of mangrove forest.Â This study took place in March and resumed in July 2010, using the method of sistematic random sampling. Observations made on Mangrove Forest National Park Alas Purwo Segara Anak in the resort Grajagan . Method of data collection with sistematic random sampling of birds carried out in the plot PUP (Permanent sampling plots) with spacing between sub plots of 50 meters and a circle with a diameter of 20 meters. The method used in necton research is sistimatic random sampling. Nekton was captured by using the net / net cash or net Jolo (local name), a circle with a diameter of 5 meters in stocked stocking density 30 times with 2 replications, namely in the morning is when the tide and the afternoon at high tide the second. The result showed that the species - bird species found at the location of permanent plots as many as 21 family with 23 species of birds while for nekton found 10 fish species from 10 family, 2 species of shrimp from one family and 1 species of crabs from 1 family. From the analysis by using the Shannon index for the degree of diversity, richness and evenness of species diversity of birds and nekton are quite high. Regression analysis showed that there is a relationship between vegetation diversity and density of birds feed on animal biodiversity, while physical environmental factors also have a relationship with a diversity of nekton.Â